The effect of fatigue on multifinger co-ordination in force production tasks in humans - Danion, F (Blackwell Science Inc, 2000)
1. This study investigated the effects of fatigue, induced by production of maximal isometric force for 60 s with four fingers, upon indices of multifinger co-ordination. 2. Measurements of individual finger forces were performed during single- and multifinger maximal force production (maximal voluntary contraction, MVC) for two sites of force application, the middle of the distal or the middle of the proximal phalanxes. Two fatiguing exercises were used, involving force production at the distal phalanxes and at the proximal phalanxes. Fourteen subjects were tested. 3. The total force in four-finger tasks dropped by about 43 % when it was produced at the site involved in the fatiguing exercise. During force production at the other site, MVC dropped by 23 %. During single-finger MVC tests, force drop with fatigue was similar across all four fingers (about −25 % of their corresponding MVCs). 4. Force production by one finger was accompanied by involuntary force production by other fingers (enslaving). Enslaving remained unchanged by fatigue when measured during force generation at the site involved in the fatiguing exercise, but increased during force production at the other site. 5. The total MVC of four fingers acting in parallel was smaller than the sum of the MVCs of these fingers in single-finger tasks (force deficit). The force deficit increased with fatigue. Force-sharing patterns during four-finger tasks showed only minor changes under fatigue. 6. These results indicate that the effects of fatigue were not limited to changes in the force-generating capabilities of the muscles. In particular, fatigue could lead to a reorganisation at a neural level that defines commands to individual fingers.